Misery loves company: Exogenous shocks in retirement expectations and social comparison effects on subjective well-being - Raymond Montizaan; Maarten C. M. Vendrik (Institute for the Study of Labor (IZA), 2012)
This study investigates the effects of social comparisons accompanying a substantial reform of the Dutch pension system on the job satisfaction of workers who are close to retirement. The reform implies that public sector workers born on January 1, 1950, or later face a substantial reduction in their pension rights, while workers born before this threshold date can still retire under the old, more generous rules. Using unique matched survey and administrative panel data on male public sector workers born in 1949 and 1950, we find strong and persistent effects on job satisfaction that are sizable compared to income effects on well-being. The drop in satisfaction is strongly affected by social comparisons with colleagues. Treated workers are less affected by the reform when the treatment group is larger in the organization where they are employed. Moreover, the social comparison effect is especially prevalent in organizations that stimulate their employees to work in teams. We also find evidence that workers compare their own replacement rate with the average replacement of comparable individuals in their organization, but the major part of the social comparison effect is non-monetary.
Keywords: D63; D1; I3; J26; 330; social comparison; well-being; retirement; Ältere Arbeitskräfte; Arbeitsbedingungen; Zufriedenheit; Rentenreform; Öffentlicher Dienst; Niederlande